Diversité Et Dynamique Des Communautés De Vers De Terre De Trois Formations Végétales Dans Une Savane Humide De l’Afrique De l’Ouest (Lamto, Côte d’Ivoire) - Madjima, Soro Nounfro; Moïse, Ehouman N’guetta; Mamadou, Toure; Doudjo, Ouattara Noufou; Seydou, Tiho (European Scientific Journal, ESJ, 2018)
The maintenance and stability of many terrestrial ecosystems are in part related to the ecosystem functions and services of soil organisms. The present study aims to evaluate the influence of litter biomass produced by three types of vegetation in the Lamto reserve on the dynamics of earthworm community. Each vegetation formations has been subdivided into 3 parcels. These parcels were geo-referenced using a GPS and mapped using QGIS software. For each plot, 25 points were randomly selected using their GPS coordinates. The litters were collected by manual collection to evaluate their biomass. Monoliths of the TSBF (Tropical Soil Biology) type were dug in order to collect the earthworms by direct manual sorting. Also, soil clumps were collected to determine the organic matter levels by the method of lossto-fire. In total, 12 species of earthworms belonging to 3 ecological categories were collected. The forest block had the highest density of earthworms with a predominance of epigeic earthworms followed by grassy savannah with a predominance of endogeic earthworms. The wooded savannah has the lowest density of earthworms with a predominance of anecic earthworms. In terms of species richness, the grassy savannah contained the greatest number of earthworm species followed by the wooded savannah and the forest block that had the same number of species. In the three vegetations formations, it was found that earthworm densities were correlated with litter biomass as well as organic matter levels (correlation between earthworm density and litter biomass: r 2 =0, 75; correlation between density of earthworms and the rate of organic matter: r 2 =0, 93).